Nation branding of Kazakhstan among international stakeholders - Tskhe, Yekaterina; San José Iglesias, Rafael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis provides a comprehensive analysis of Kazakhstan's branding efforts and their impact on international perceptions. Through a mixed-methods approach, including in-depth interviews with experts and a survey of international stakeholders, the research within this thesis identifies key elements influencing Kazakhstan's nation brand, such as cultural heritage, economic development, political stability, and international relations. The main added value of this thesis are practical insights for policymakers, branding strategists, and international relations experts, highlighting the need for a sophisticated and strategic approach to nation branding. By understanding the successes and pitfalls of Kazakhstan's nation branding efforts, valuable lessons can be drawn that are applicable to other nations with similar goals or challenges.
Vedoucí práce: Rafael San José Iglesias
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses